ANALYSIS OF THE EFFECT OF COMPETENCE AND ACHIEVEMENT OF KPI TARGETS ON EMPLOYEE PERFORMANCE AT PT BANK MEGA SYARIAH BANDAR LAMPUNG BRANCH OFFICE - Khaidarmansyah; Princess Rosmala Dewi (SEAN Institute, 2022)
This study aims to determine the effect of Competence on Employee Performance, KPI Achievement Target on Employee Performance, and Competence and KPI Achievement Target on Employee Performance at Bank Mega Syariah Bandar Lampung Branch Office. This research is quantitative descriptive. The population in this study were all employees of Bank Mega Syariah Branch Office Bandar Lampung. The sample of this study amounted to 30 which were determined using the saturated sampling technique. The data collection technique used is the distribution of questionnaires,document recording, and interviews, then the data were analyzed using multiple linear regression analysis. The results of the study indicate that Competence partially affects employee performance, KPI Achievement Target partially affects employee performance, and Competence and KPI Achievement Target simultaneously affect employee performance at Bank Mega Syariah KC Bandar Lampung.